Profile of intestinal parasitoses in the elderly in Brazil: a literature review in the last ten years (Research, Society and Development, 2020)
Aging leads to a progressive reduction in physiological capacity and a decrease in the ability to respond to environmental stress, leading to an increase in susceptibility and vulnerability to diseases, especially as parasites. Parasitosis  is the term used to define any condition caused by parasitic agents, including their pathological manifestations.The objective of this study was to describe the epidemiological profile of intestinal parasitic infections that affect the elderly in Brazil in the last 10 years and to catalog which are the main parasites in greater prevalence and why they affect the elderly in the regions of the country. The study was carried out through an integrative literature review without the application of meta-analysis on the theme of intestinal parasites in Brazil in the years 2009 to 2018.This study of the articles showed that parasitological samples from the elderly, aged 65 to 80 years, female and male, living in nursing homes in the urban area, with a higher prevalence of the parasites Entamoeba coli and Endolimax nana and The most used technique was Hoffman's.There is a need for more complete studies on the situation of the prevalence rates of intestinal parasitosis in the elderly in Brazil, given the scarcity of studies focused on the topic in question.